Identifikasi Nematoda pada Lahan Kebun Raya Banua Banjarbaru, Kalimantan Selatan - Auliya Hanifa Permata; Dewi Fitriyanti; Abdul Gafur (Universitas Lambung Mangkurat, 2021)
This research is to identify soil nematodes in Kebun Raya Banua in the province of South Kalimantan. Soil samples were taken to a depth of 0-20 cm. Nematodes extraction were conducted using Whitehead and Hemming method. Nematodes were killed by hot formaline. Permanent slides were prepared using Seinhorst (1962) method. Identification was carried out using a microscope with up to 1000x magnification. Two genera of the Order Dorylaimida (Aporcelaimellus and Xiphinema), one genus of the Order Monochida (Iotonchus), and one genus of the order Tylenchida (Criconema) were found.